Workshop Pengembangan Pembelajaran Melalui Spada Sebagai Penguatan SPMI Pascasarjana Universitas Mataram - Muh. Makhrus; Suherman Suheri; Kosim (Universitas Mataram, 2021)
Mataram University through the Center for Technology and Computer Science and the Institute for Quality Assurance and Educational Development has developed online learning through SPADA UNRAM. Based on the observations of the Postgraduate Quality Assurance Group, the use of online learning through SPADA UNRAM by lecturers in the Postgraduate environment is still below 50% of the number of available courses. Online learning conducted by lecturers is still focused on using the zoom application. Online development workshops have been carried out by the Quality Assurance Group for lecturers at the Postgraduate University of Mataram through service activities that focus on training on the use of the UNRAM SPADA platform and training on the development of learning management systems (LMS) at SPADA UNRAM . The workshop activities were carried out for 3 (three) days, namely from August 4-6, 2021 with the aim of increasing the number of courses developed by lecturers through SPADA UNRAM, so that they could support SPMI in Postgraduate. On August 4, 2021, a workshop was opened and the delivery of online learning development materials through SPADA UNRAM was held. Meanwhile, the assistance for the development of online learning is carried out for 2 days, from 5-6 August 2021 with each study program in the Postgraduate environment accompanied by a lecturer/resource person. The results of the workshop activity showed an increase in the content of the material on the LMS which was getting better for courses in study programs in the Postgraduate environment that already existed at SPADA and the addition of new courses developed at SPADA UNRAM.